Definition of reliable reliability of single technical information security from the real attack attempts - ЖУРИЛЕНКО, Борис Евгенович (Ukrainian Scientific Journal of Information Security, 2013)
The as a result conducted work the offered method for determination of reliable reliability of technical defence of information on the basis of the real attempts of breaking in. The offered method allows to estimate reliable reliability of the single systems of defence, and during setting of her on a few objects to foresee not only an attempt but also time at which reliable breaking in on other objects.